2021
DOI: 10.3390/agriculture11111052
|View full text |Cite
|
Sign up to set email alerts
|

How to Promote Medium-Sized Farms to Adopt Environmental Strategy to Achieve Sustainable Production during the COVID-19 Pandemic?

Abstract: To achieve sustainable production in medium-sized farms, this research proposes a hierarchical linear modeling (HLM) to predict environmental strategy (ES), which is a crucial source of sustainable production. Based on the theory of upper echelons, the present research puts forward that the environmental leadership (EL) of the chief executive officer (CEO) at phase one affects the development of environmental corporate social responsibility (ECSR) adoption, which in turn affects the development of ES adoption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In terms of a sustainable approach, food manufacturers generate various ecological effects [13][14][15][16][17][18][19][20][21], and it the need for a sustainable process is recognized [22][23][24][25][26][27][28][29][30][31][32], including the production of CO 2 [33]. Approximately 40% of the food destined for human consumption ends up as waste during the manufacturing [34] and consumption process [35].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of a sustainable approach, food manufacturers generate various ecological effects [13][14][15][16][17][18][19][20][21], and it the need for a sustainable process is recognized [22][23][24][25][26][27][28][29][30][31][32], including the production of CO 2 [33]. Approximately 40% of the food destined for human consumption ends up as waste during the manufacturing [34] and consumption process [35].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental policies can respond to increased competition, consumer demand, and product quality because the environmental image of firms meets stakeholder expectations. Previous research also indicated that environmental policies could increase competitive advantage [44][45][46].…”
Section: The Environmentally Proactive Strategy Adoption and Financia...mentioning
confidence: 96%
“…Past research proposes that leadership is regarded as an important characteristic of leaders [2], so sustainable leadership will influence environmental inno-vation strategies. In addition, the chief executive officer controls most of a company's manpower and resources, so the chief executive officer's preference for sustainable development will affect which corporate activities are invested in [35][36][37], which in turn affects the company's willingness to adopt environmental strategies. Indeed, past studies have found a similar result and propose that sustainable leadership can lead to innovative employee behavior [38].…”
Section: Sustainable Leadership and Environmental Innovation Strategymentioning
confidence: 99%